Local community’s cultural attitudes towards support for tourism development and conservation in archaeological heritage of the Lenggong Valley - Abas, Siti Aisah; Mohd Aziz, Nur Afiqah; Abd Rahman, Nur Hidayah; Md Sawari, Siti Salwa; Ghoitsa Rohmah, Nurazizah (Taylor and Francis Group London, 2021)
Overdevelopment not only affects the urban landscape but also not acceptable for any tourism region, particularly for the protected area. Local communities are terrified to lose their local authenticity due to the external influence and visitor’s disturbance. This research endeavours to explore the cultural attitudes and local community participation in the Archaeological Heritage of the Lenggong Valley. Employing a quantitative research design, a total of 121 survey questionnaires were administered to the residents of Lenggong Valley. The samples were selected using a random sample technique. As a result, the data revealed that cultural attitudes in the host community are positive. Most of them strongly support the conservation of culture and heritage in the Lenggong Valley. Furthermore, the results also showed that the positive benefits outweigh the negative effects of tourism. Further research on the variations in cultural attitudes based on socio-demographic features that have helped confirm theories related to the social impact of tourism, such as the theory of social change, may further explore possible reasons for these communal attitudes.